Emerging Nano/Micro-Structured Degradable Polymeric Meshes for Pelvic Floor Reconstruction - Kallyanashis Paul; Saeedeh Darzi; Jerome A. Werkmeister; Caroline E. Gargett; Shayanti Mukherjee (Nanomaterials, 2020)
Pelvic organ prolapse (POP) is a hidden women’s health disorder that impacts 1 in 4 women across all age groups. Surgical intervention has been the only treatment option, often involving non-degradable meshes, with variable results. However, recent reports have highlighted the adverse effects of meshes in the long term, which involve unacceptable rates of erosion, chronic infection and severe pain related to mesh shrinkage. Therefore, there is an urgent unmet need to fabricate of new class of biocompatible meshes for the treatment of POP. This review focuses on the causes for the downfall of commercial meshes, and discusses the use of emerging technologies such as electrospinning and 3D printing to design new meshes. Furthermore, we discuss the impact and advantage of nano-/microstructured alternative meshes over commercial meshes with respect to their tissue integration performance. Considering the key challenges of current meshes, we discuss the potential of cell-based tissue engineering strategies to augment the new class of meshes to improve biocompatibility and immunomodulation. Finally, this review highlights the future direction in designing the new class of mesh to overcome the hurdles of foreign body rejection faced by the traditional meshes, in order to have safe and effective treatment for women in the long term.